Design of a Three-Layer Blockchain Integrity Validation Model for Fraud Prevention in Business Licensing Platforms - Edrian Hadinata; Tasya Febriyanti (STMIK Methodist Binjai, 2026)
Data integrity in multi-stage government licensing services is a critical challenge, particularly when each stage involves different actors with distinct authority. Without a permanent recording mechanism for every action in the workflow, licensing data remains vulnerable to manipulation. This study develops a web-based SIUP business licensing information system integrating blockchain technology as an automatic integrity validation mechanism. Every action taken by six actors is permanently recorded as a new block using SHA-256 hashing and Proof-of-Work requiring hash values prefixed with